Analysis of Construction Monitoring and Control of Tunnels Crossing Broken Faults and Water-rich Geology. Issue 1 (January 2022) - Fang, Jingang
Abstract: In view of the poor geology such as tunnel engineering crossing faults or passing faults, the construction of surrounding rock and support is complicated. During construction, it is necessary to ensure the stability of the surrounding rock and supporting system, and ensure the timing of the secondary lining construction. For this reason, through the analysis and processing of monitoring data, the law of stratum change is mastered, and the supporting parameters and construction methods are adjusted and revised at the same time, so as to provide the best information for the tunnel surrounding rock and supporting lining construction.